2013
DOI: 10.1177/0011392113516651
|View full text |Cite
|
Sign up to set email alerts
|

Do ‘cultures of life satisfaction’ travel?

Abstract: This article explains the variation in the life satisfaction of international migrants across Europe using the idea of the cultural embeddedness of subjective well-being, expressed in various approaches such as social comparison theory, the Easterlin paradox and Cummins' (2003) assumption of normativeness. The authors claim that immigrants' levels of life satisfaction will be the subject of a dual contextuality. First, the cultural heritage of the country of origin has a pervasive influence long after migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
2
18
2
1
Order By: Relevance
“…In the case of migrants from France, where social trust levels are low, this pattern is consistent with what would be predicted by other studies showing that migrants have social trust assessments partway between those in their countries of birth and of residence (Dinesen, 2012;Soroka et al, 2007;Rice and Feldman, 1997). Similar results for life satisfaction, which depends heavily on social trust, have also been achieved using data from the European Values Survey, showing life satisfaction for European migrants tended to be an 'alloy' incorporating the levels in both the host and origin countries (Voicu and Vasile, 2014). Helliwell, Wang and Xu (2016) test the relative importance of culture versus experience by examining the immigration footprints for social trust, generosity, and confidence in specific national institutions, making use of a fully global sample involving immigrants to and from more than 130 countries.…”
Section: Literature Reviewsupporting
confidence: 90%
“…In the case of migrants from France, where social trust levels are low, this pattern is consistent with what would be predicted by other studies showing that migrants have social trust assessments partway between those in their countries of birth and of residence (Dinesen, 2012;Soroka et al, 2007;Rice and Feldman, 1997). Similar results for life satisfaction, which depends heavily on social trust, have also been achieved using data from the European Values Survey, showing life satisfaction for European migrants tended to be an 'alloy' incorporating the levels in both the host and origin countries (Voicu and Vasile, 2014). Helliwell, Wang and Xu (2016) test the relative importance of culture versus experience by examining the immigration footprints for social trust, generosity, and confidence in specific national institutions, making use of a fully global sample involving immigrants to and from more than 130 countries.…”
Section: Literature Reviewsupporting
confidence: 90%
“…Both measures only provide a rough estimate of attitudes in the origin and recipient countries and thus are not directly tied to individual respondents. However, similar measures have been used in other studies that compare migrants' attitudes from a socialisation perspective (Dinesen 2012;Reeskens & van Oorschot 2015;Röder & Mühlau 2014;Seibel & Hedegaard 2017;Voicu & Vasile 2014). A comparative study also shows that this method does not overestimate the acculturation of immigrants, as has been speculated by some (Hedegaard & Bekhuis 2018).…”
Section: Variablesmentioning
confidence: 81%
“…Given that it is unlikely that migrants select their new countries on the basis of gender values, this has been interpreted as an adaption effect. The two approaches are drawn together by Voicu and Vasile (2014), who found that migrants' life satisfaction is affected by the general level of life satisfaction in both the origin country and the recipient country. They argued that acculturation to new attitudes is therefore dependent on the frames of reference of both the origin country and the recipient country, as well as the ties to both contexts.…”
Section: Theory On Determinants Of Meritocratic Attitudesmentioning
confidence: 99%
“…We cannot resolve this selection issue since we do not know satisfaction levels before (potential) migration to Europe. At best, we can control for observable factors (specifically education) which are likely to be linked to positive selection (Voicu and Vasile 2014). We can, however, note that personality traits are not immutable, and, unlike other studies that include migrants (and returnees), our sample has experienced many decades between the original migration decision and the current evaluation of life satisfaction, increasing the potential for adaptation to the destination context.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Various authors have stressed, however, that the classical comparison with natives provides little information on the consequences of migration itself for life satisfaction, since we do not know how satisfied they started out (Bartram 2013 a , 2013 b ; Bayram et al . 2007; Beirens and Fontaine 2011; Voicu and Vasile 2014). Rates of life satisfaction in the countries of origin are typically substantially lower on average than those in European countries.…”
Section: Introductionmentioning
confidence: 99%